Development of Students’ Critical Thinking Skills via Teaching English - Veronika Starichkova; Natalia Moskovskaya; Elena Kalinovskaya (ARPHA Proceedings, 2022)
The purpose of the research is to investigate the educational potential of the foreign language as a university subject and to verify theoretically and practically the possibility of developing critical thinking skills of students in the process of foreign language acquisition at the tertiary level of education. The student age is a sensitive period for the development of the intellectual sphere of an individual especially in general and critical thinking. The research about critical thinking suggests that this type of thinking is a category of interdisciplinary knowledge and represents a set of certain skills: reflection, goal setting, decision making, problem-solving, and other skills. Experimental teaching and practical evaluation of the methods designed to develop students’ critical thinking skills by means of the foreign language showed that in the process of specially organized teaching and educational activities, students successfully master critical thinking skills if they are taught step-by-step; learning content is thoroughly selected; an appropriate system of exercises is designed; the problem- and communication-oriented teaching is provided. It is necessary to implement the communicative approach and the approach of interrelated teaching of language skills, to ensure a close connection of the content of the exercises with students’ real life (to use exercises that allow analyzing students’ real-life situations, events, behavior, actions), to use active methods of teaching (role play, case-method, project method).